Application of Electrodepositing Graphene Nanosheets for Latent Fingerprint Enhancement. Issue 1 (12th November 2013) - Zhang, Meiqin; Zhu, Yu; Yu, Xi; Liu, Shouliang; Wang, Meiling; Wei, Qianhui; Hu, Xiaoning; Tang, Qiao; Zhao, Yanjun; Zhang, Xueji
Abstract Fingerprints are still one of the most powerful and important means of biometric identification. This paper presents a green and fast electrochemical method for improved development of latent fingerprints (LFPs) on five kinds of commonly encountered conductive substrates by the use of spatial selective electrodeposition of graphene nanosheets. Since secretions produced in the fingerprint deposit lead the underlying surface to be electrochemically inert or less active, the electrodeposition process only occurs on the areas without fingerprint residue. As a result, a high contrast negative image of the fingerprint was achieved by the electrochemical reduction of graphene oxide (GO) after optimizing the factors (applied potential, deposition time and scan rate).